Rapid Determination of Phenolic Compounds in Extracts of the Leaves of Ipomoea batatas (L.) Lam. by HPLC-DAD-ESI-MS - Qiu, Fan; Cui, Yubao; Juan Wang, Mei (Asian Journal of Chemistry, 2013)
Ipomoea batatas (L.) Lam. (Sweet potato) is not only used as staple food, but also is a traditional herbal drug in China for the treatment of various disease. For analyze the component of the extraction, we have developed a chromatography electrospray ionization tandem mass spectrometry (HPLC-ESI-MS/MS) method to characterize th fraction of ethyl acetate, which gtave prominent [M-H]– ions by electrospray ionization menitored in the negative ion mode. A total of ten phenolic compounds were identified or tentatively characterized based on the UV spectra and Tandem mass spectra of the HPLC peaks. The tandem mass spectrometric fragmentation behaviour of caffeoylqinic acid derivatives and flavonoids have been investigated extensively.